Antimicrobial Activities of New Indole Derivatives Containing 1,2,4-Triazole, 1,3,4-Thiadiazole and Carbothioamide - Süzen, Sibel (My University, 2018)
Objectives: In new antimicrobial drug development studies, indole and its derivatives create an important class of compounds. In addition, azoles and their derivatives were recognized to be associated with a variety of biologic activities such as antibacterial and antifungal. In this study antimicrobial activities of some indole derivatives mainly substituted with 1,2,4-triazole, 1,3,4-thiadiazole and hydrazinecarbothioamide were investigated to evaluate their efficacy. Materials and Methods: The efficacy of new compounds was evaluated using 2-fold serial dilutions against Staphylococcus aureus, MRSA, Escherichia coli, Bacillus subtilis, Candida albicans, and Candida krusei. Results: The MIC was determined for test compounds and for the reference standards sultamicillin, ampicillin, fluconazole, and ciprofloxacin. Conclusion: The compounds possessed a broad spectrum of activity having MIC values of 3.125-50 µg/mL against the tested microorganisms. This study provides valuable evidence that the indole-triazole derivative compound 3d holds significant promise as a novel antibacterial and antifungal lead compound.
Keywords: Indole; 1, 2, 4-triazole; 1, 3, 4-thiadiazole; MRSA, C. krusei